DETERMINAN KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI WILAYAH KOTA TANGERANG TAHUN 2023 - Laurensia, Olta; Rosyadi, Mohammad Eddy (E-Jurnal Akuntansi TSM, 2023)
This research aims to obtain empirical evidence regarding the effect of implementation E Biling system, E-Filing system, taxpayer understanding, taxpayer awareness, taxpayer environment, tax socialization, and tax sanctions on individual taxpayer compliance in the Tangerang City area. This research data was obtained through distributing the questionnaires at KPP Pratama West Tangerang and Kosambi. The questionnaire collection process was carried out from November 9 2023 to December 1 2023. Non-probability sampling method is used in taking research samples with a total of 96 data that matched the criteria. Hypothesis testing used to determine the effect of each independent variable on individual taxpayer compliance is a multiple regression model. The results of this research indicate that the application of E-Filing system, taxpayer understanding and taxpayer awareness influence individual taxpayer compliance. The other four independent variables, namely the implementation of E-Biling, taxpayer environment, tax socialization, and tax sanctions have no influence on individual taxpayer compliance.